Sucralose Promotes Colitis-Associated Colorectal Cancer Risk in a Murine Model Along With Changes in Microbiota - Li, Xueting; Liu, Yuanli; Wang, Yan; Li, Xue; Liu, Xinran; Guo, Mengru; Tan, Yiwei; Qin, Xiaofa; Wang, Xiuhong; Jiang, Mingshan (Frontiers in Oncology, 2020)
Sucralose is a calorie-free high-intensity artificial sweetener that is widely used in thousands of foods and beverages all over the world. Although it had been initially regarded as a safe inert food additive, its adverse effect on gut microbiota and health has drawn more and more attention as evidence accumulates. Studies by us and others revealed that sucralose exacerbated gut damage and inflammation in animal models for inflammatory bowel disease (IBD) including both for ulcerative colitis and Crohn’s disease. Our study demonstrated that sucralose greatly aggravated dextran sulfate sodium (DSS) - induced colitis along with changes in gut microbiota, gut barrier and impaired inactivation of digestive proteases mediated by deconjugated bilirubin. It is well documented that IBD greatly increase the risk of colorectal cancer (CRC), the globally third most common cancer that, just like IBD, has high rate in the developed countries. Azoxymethane (AOM)/DSS has been the most commonly used animal model for CRC. In this study, we further explored the effect of sucralose on tumorigenesis and the possible mechanism using the AOM/DSS mice model. At first, 1.5 mg/ml sucralose was put in the drinking water for 6 weeks to reach a relatively stable phase of impact on gut microbiota. Then 10 mg/kg AOM was administrated through intraperitoneal injection. 7 days later, 2.5 % DSS was put in drinking water for 5 days, followed by 2 weeks without DSS. Then the 5 days DSS was repeat for another time and the mice were sacrificed 7 weeks after AOM injection. The results showed that sucralose caused significant increases in the number and size of AOM/DSS induced colorectal tumors along with changes of other parameters such as body and spleen weight, pathological scores, mortality, fecal digestive proteases, gut barrier molecules, gut microbiota, inflammatory cytokines and pathways (TNFα, IL-1β, IL-6, IL-10, and TLR4 / Myd88 / NF-κB signaling), and STAT3/VEGF tumor-associated signaling pathway molecules. These results suggest sucralose may increase tumorigenesis along with dysbiosis of gut microbiota, impaired inactivation of digestive protease, damage of gut barrier, and exacerbated inflammation.